Wage premia for newly hired employees: Theory and evidence - Patrick Kampkötter; Dirk Sliwka (Institute for the Study of Labor (IZA), 2011)
We investigate wage differences between newly hired and incumbent employees. We show in a formal model that when employees care for wages as well as match-specific utility, incumbents earn less than new recruits if and only if firm-specific human capital is not too important. The existence and structure of these wage premia is then investigated empirically using detailed personnel data from a large number of banks. We find that, on average, new hires earn more than comparable incumbent colleagues on the same job. But the size of the wage premia varies between jobs and indeed strongly depends on a measure of human capital specificity.
urn:nbn:de:101:1-201104133406
Keywords: J31; J44; J62; 330; wages; job mobility; wage premia; human capital; new hires; Lohnstruktur; Bankberufe; Personalbeschaffung; Arbeitsmobilität; Betriebszugehörigkeit; Humankapital; Finanzsektor; Schätzung; Deutschland